Learn from the Experts about Being a New Manager Michael Lopp - Lopp, Michael (O'Reilly Media, Inc., 2018)
Learn from the Experts is a series where we sit down with leading industry practitioners and ask them for real-world stories and examples of how they're using technology in their everyday work. In this Learn from the Experts interview, Laurel Ruma talks to Michael Lopp about being a new manager.
Online resource; Title from title screen (viewed February 2, 2018)
Keywords: Internet videos; Streaming video; Vidéos sur Internet; Vidéo en continu; streaming video; Electronic videos